G444(P) An audit of the management of anaphylaxis in children in a district general hospital. (27th April 2015) - Mclaughlin, C; Costa, J; Aralihond, A
Abstract : Aims: To assess how management of anaphylaxis in children complies with local and national guidance. Methods: Retrospective review of 20 cases of paediatric anaphylaxis, diagnosis agreed by consensus between two physicians. Results: Features of the acute reaction were well documented (Figure 1 ). However only 75% of children had their blood pressure recorded. The circumstances around the reaction were also well documented and likely triggers identified in all cases. 95% implicated a food allergen; 63% of these were nuts or nut–containing products. 85% of children received IM adrenaline, mostly pre-hospital and often by parents (Figure 2 ). Steroids formed part of the acute management in 95% of cases, and antihistamines in 100%. 75% of children were discharged with a course of steroids and antihistamines. The clinical timescale was less well recorded; 30% did not have the time of the onset of the reaction documented, and 27% of children who received pre-hospital adrenaline did not have the time documented. All children were observed for 6 h minimum. Documentation of counselling was poor with only 35% receiving allergen avoidance advice and 20% warned about the possibility of biphasic reaction. An adrenaline auto–injector (AAI) was offered to 70%. 57% of those received a documented explanation and demonstration of its use. 95% were discharged with a GP letter and 80% had a specialist allergy referral. Discussion and conclusion: The results revealed opportunities for improvement. There is a high standard of history-taking and examination, though an estimated timescale is often not obtained and blood pressure is not consistently measured. Documentation of counselling needs improvement. The pharmacological management of anaphylaxis is excellent in the acute setting but substandard at discharge with children leaving hospital without antihistamines, oral steroids and most importantly AAIs. The proportion receiving prompt pre-hospital treatment with their own AAIs highlights their usefulness and the need to ensure they are prescribed to children at risk. Overall there is good adherence to guidance but simple measures such as a proforma, patient leaflet and personalised allergy action plan available for printing with the local guideline could further optimise patient care. A re-audit to assess the impact of these interventions is planned for 2015.